Interactive Mobile Applications to Support the Teaching of Reading and Writing of Spanish for Children in Primary Education - Hernández-Campos, Eduardo; Jaimez-González, Carlos R.; García-Mendoza, Betzabet (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In the educational process, literacy is considered as a fundamental part, which focuses on the ability to read and write. Reading and writing are processes that, although they have features in common, they may not be developed in parallel, but both are encompassed in teaching methods that aim to develop these two skills at the same time. Interactive mobile applications can be part of a strategy to support the teaching of reading and writing skills. This paper presents a review of five interactive mobile applications to support the teaching of Spanish reading and writing skills. Mobile applications were analyzed based on their general features and the activities they have. The following general features were taken into consideration: the existence of voice assistants, supporting characters, language selection, progression of activities, creation of avatars, variable difficulty, progress panel, images, among others. The activities considered for the revision were those that allow completing syllables, completing words from letters, completing words from syllables, completing sentences, relating images to words, among others.